Assessment of the H‐reflex at two contraction levels before and after fatigue. (16th February 2016) - Stutzig, N.; Siebert, T.
Abstract : The aim of the present study was to compare the H‐reflex evoked at rest and at 20% maximal voluntary contraction (MVC) prior to and after fatiguing the lateral gastrocnemius (LG). The maximal H‐reflex and M‐wave were recorded in the LG, and soleus (SOL). Electrical evoked potentials were delivered to the posterior tibial nerve when muscles were inactivated and at 20% MVC. After fatigue, the Hmax /Mmax ratio of the fatigued LG was increased for both contraction levels (rest and 20% MVC) and remained unaltered for non‐fatigued SOL. Before fatigue, the Hmax /Mmax ratio of SOL was enhanced at rest compared with the Hmax /Mmax ratio at 20% MVC. No differences were observed for LG. Fatigue of a single muscle leads to increased spinal reflex activity of the homonymous muscle. Contrary to previous recommendations in the literature, there appears to be no benefit with regard to the H‐reflex amplitude in evoking electrical potentials during constant voluntary contractions at 20% MVC compared with inactivated muscles. The observed difference in SOL prior to fatigue was most likely due to hyperpolarization of the muscle fiber membrane.